Can Skill Diversification Improve Welfare in Rural Areas? Evidence from the Rural Skills Development Project in Bhutan - Natalie Chun; Makiko Watanabe (Asian Development Bank (ADB), 2011)
Income growth in rural areas may be one of the greatest challenges to further poverty reduction and economic development. Using a new survey of rural Bhutanese households we investigate the short-term economic, social, and psychosocial benefits of a vocational skills training program that was intended to help diversify incomes into sources outside of agriculture; and the determinants of participation. We find limited positive impacts of the program along various economic, social, and psychosocial dimensions, but find evidence that it helped to diversify household incomes into these skill areas. Further, evidence suggests that those who underwent longer training were more likely to have better job opportunities. This suggests that: (i) there is a need to place a greater emphasis on creating a mechanism to connect the training program to income-generating opportunities such as job placement services and entrepreneurship or mentoring services support for the program to have a more immediate effect; and (ii) there is a need to refine the curriculum and extend the training time to allow trainees to develop their skills. Increased income or starting a business, in turn, is likely to have a positive psychosocial impact on the trainees. Moreover, we find that married people and females are significantly less likely to participate, after including other key factors, indicating that there is need to provide more femalefriendly training with flexibility in training time and venues, and with training in other skill areas so that there will be more equality in the skill development process.
hdl:11540/2022
Keywords: I38; J24; 330; training; skill diversification; nonfarm sector; development economics; Bhutan; Entwicklungspolitik; Arbeitsmarktpolitik; Haushaltseinkommen; Bildungsertrag; Beschäftigungseffekt; Soziale Lage; Privater Haushalt; Ländlicher Raum; Bhutan